Organizing teachers in Pennsylvania, 1935–1941. (3rd September 2019) - Toloudis, Nicholas
ABSTRACT: By eliminating mandatory agency fees, the US Supreme Court's Janus decision has created an opportunity for the American teachers' unions to renew their commitment to organizing teachers. This article returns us to the pre-agency fee era, when on-the-ground organizational work was essential for building teachers' unions. Drawing from archival documents, it shows how dedicated activists from Philadelphia and Pittsburgh reached out to Pennsylvania's classroom teachers to draw them into the AFT during the later Depression years. It details the changes in their organizational strategy, the challenges organizers faced in the field, their successes and failures, and the work accomplished by a paid AFT organizer – Vivian Dahl – in 1938. Above all, it documents both the dividends of face-to-face interactions between organizers and prospective unionists and the difficulties of such work in an ideologically polarized political environment, among a group of workers dominated by the hierarchical ethos of professionalism.